2001
DOI: 10.1021/jp0038456
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry-Selective Observation of the N 1s Shape Resonance in N2

Abstract: Inner-shell photoelectron spectra of the N 1s level in N 2 have been measured with sufficient resolution to resolve the splitting between the gerade and ungerade components. The selective enhancement of the gerade component on the N 2 σ shape resonance is clearly seen, confirming that the resonant behavior is mainly caused by the σ u channel. The splitting of the two components is found to be 97(3) meV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
82
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(97 citation statements)
references
References 42 publications
13
82
2
Order By: Relevance
“…However, with the third generation storage rings the resolution was pushed to a level where the σ g and σ u states of the C1s ionization in C 2 H 2 could be fully resolved, see Fig.9. Similar splittings have recently been seen for N1s in N 2 [46] and in a few other cases.…”
Section: Broadening Due To Partial Core Hole Delocalizationsupporting
confidence: 86%
See 1 more Smart Citation
“…However, with the third generation storage rings the resolution was pushed to a level where the σ g and σ u states of the C1s ionization in C 2 H 2 could be fully resolved, see Fig.9. Similar splittings have recently been seen for N1s in N 2 [46] and in a few other cases.…”
Section: Broadening Due To Partial Core Hole Delocalizationsupporting
confidence: 86%
“…With the use of third-generation synchrotron radiation facilities it was possible to partly resolve this splitting [84] in the case of the C1s level of acetylene. So far it has only in a few cases been possible to identify such a splitting, most reports have concerned C 2 H 2 [47,85] and N 2 [46]. In section 3.5 above we showed the result from ref.…”
Section: Interference Phenomena In Soft X-ray Photoelectron Spectroscopymentioning
confidence: 71%
“…In particular, a wealth of experimental and theoretical data has been published for total cross sections corresponding to core as well as valence-shell photoionization of the prototype N 2 1-35 and CO 1,2,5,6,12,13,34,[36][37][38][39][40][41][42][43][44][45][46][47][48][49] molecules, from the ionization threshold up to a few tens of eV above it. More recently, the advent of high-brilliance 3rd-generation synchrotron radiation sources in combination with high energy-resolution detection techniques has opened the way for the determination of vibrationally resolved photoionization spectra of these molecules, both at low and high photon energies 30,35,38,39,[50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] . These experimental achievements have fostered the development of new theoretical methods that, in addition to accounting for electronic degrees of freedom, are also able to describe the molecule's vibrations 13,30,35,…”
Section: Introductionmentioning
confidence: 99%
“…Another state which exhibits similar behavior at the shape resonance is the X-state with two vacancies in the 3σ g orbital 1 Σ + g . Measurement of the N1s photoelectron spectrum of N 2 as a function of photon energy distinguished the gerade and ungerade components and followed the cross sections for each component separately [61]. A later study confirmed that the shape resonance has σ u symmetry and couples primarily to the σ g channel, but inter-channel coupling leads to resonant behavior even in the σ u channel [62].…”
Section: Above Threshold Resonancesmentioning
confidence: 92%